Performance Differences in Europe: Tentative Hypotheses on the Role of Institutions - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 2007)
Low growth and persistently high unemployment in Europe raised the question whether it was the specific features of the European Social Model, which lead to these disappointing results. This paper defines the characteristics of the model, and the differences between submodels applied in different European countries. Then it carves out the specific characteristics of the Nordic European Model, and its changes in economic policy and strategy which made these countries successful over the past ten to fifteen years - after the same countries had experienced recurrent crises in the decades before. Specifically, we look at the role of institutions and their changing priorities for making the Scandinavian countries better able to cope with change as compared to Germany, Italy and France.
Keywords: 330; Welfare models; corporatism; economic performance; models of capitalism; Korporatismus; Kapitalismus; Institutionelle Infrastruktur; Sozialstaat; EU-Staaten